Morfo-anatomia, dormência, germinação e emergência de plântulas de tento (Ormosia paraensis Ducke – Fabaceae) - Silva, Breno Marques da Silva e [UNESP] (2010)
Ormosia paraensis Ducke, known as “tento”, possess seeds used to make handicrafts and wood worked by furniture makers. For the forest identification and seeds technology, the information on the biology and therefore for the production of “tento” seedlings are incipient. Thus, the aim of this study was the morpho-anatomical description as well as determining the most appropriate methods for overcoming dormancy, germination and seedling emergence of “tento”. For the morpho-anatomical description, the evaluations were examined by optical and scanning electron microscopy. For the dormancy break of the seeds, the methods were physical and chemical scarification. For the temperature, substrate and depth evaluation were used temperatures from 5 to 45 oC, the substrates sand, paper, vermiculite and PlantmaxR and the depths of 0, 2 and 4 cm. The fruit is a nutant legume, brown to black, dehiscent and with one or two seeds of lateral placentation. The seeds are bitegmic, exalbuminous and rounded. The seedlings have simple and alternate leaves, and their germination is hypogeal cryptocotyledonary. The mechanical scarification and the chemical by sulfuric acid immersion for 60 or 120 minutes are suitable for overcoming seed dormancy. The range of the optimum temperature for germination is between 25 and 35 oC between sand or paper. In the nursery are sand and vermiculite, sowings higher than 2 cm depths are unsuitable for seedling emergence